Evolution of Direct Discourse Marking from Classical to Late Latin - Mikulová, Jana, (The Language of Classical Literature ;, 2022)
Changes in the marking of direct discourse show us the vitality of Latin and the creativity of Late Latin authors, who were able to integrate two potentially conflicting traditions - "classical" and "biblical".